Gender roles and activities among the rural poor households: Case studies from hill villages - Pokharel, Binod (Occasional Papers in Sociology and Anthropology, 2008)
The PDF of this file is 2,520 kbytes in size and therefore will take a long time to download if you click on the PDF link below. If you would like the file to be sent to you by email, please send a request to info@nepjol.info. Please include the citation below in your request. DOI: 10.3126/opsa.v7i0.1111 Occasional Papers in Sociology and Anthropology Vol.7 2001 p.65-82